DIGITALIZATION - AS THE MAIN FACTOR IN THE DEVELOPMENT OF THE QUALITY MANAGEMENT SYSTEM OF THE TEXTILES INDUSTRY OF THE REPUBLIC OF UZBEKISTAN - Khalilov Nurullo Khamidillayevich; Safina Nafisa Talgatovna (Scholar Express Journals, 2023)
In this article are discussed the impact of digitalization of the economy of the Republic of Uzbekistan on the development of a quality management system for the textiles industry.
Keywords: digitalization; Industry 4.0; quality; quality management system